GUYS PLEASE HELP ME HELP HELP PLEASE PLEASE!!! Simplify and solve for the unknown. Use order of operations as needed. Check your work.

Type the FULL answer in the box, using the variable and an equal sign. Do not add any spaces.

5(B + 3) = 4(B – 7) + 2B

Respuesta :

The solution is B = 43

Step-by-step explanation:

Simplify and solve for the unknown for 5(B + 3) = 4(B - 7) + 2B

  • Simplify each side
  • Add the like terms in each side if need
  • Separate the unknown in one side and the numerical term in the other side to find the value of the unknown

∵ 5(B + 3) = 4(B - 7) + 2B

- Multiply the bracket (B + 3) by 5 in the left hand side and multiply

  the bracket (B - 7) by 4 in the right hand side

∵ 5(B + 3 ) = 5(B) + 5(3) = 5B + 15

∵ 4(B - 7) = 4(B) - 4(7) = 4B - 28

∴ 5B + 15 = 4B - 28 + 2B

- Add the like terms in the right hand side

∵ 4B + 2B = 6B

∴ 5B + 15 = 6B - 28

- Add 28 to both sides

∴ 5B + 43 = 6B

- Subtract 5B from both sides

∴ 43 = B

- Switch the two sides

∴ B = 43

To check the answer substitute the value of B in each side if the two sides are equal then the solution is right

The left hand side

∵ 5(43 + 3) = 5(46) = 230

The right hand side

∵ 4(43 - 7) + 2(43) = 4(36) + 86 = 144 + 86 = 230

∴ L.H.S = R.H.S

∴ The solution B = 43 is right

The solution is B = 43

Learn more:

You can learn more about the solution of an equation in brainly.com/question/11229113

#LearnwithBrainly

ACCESS MORE